Розвиток концепції смартспеціалізації: теоретичні аспекти - Швець, Н.В. (Управління економікою: теорія та практика, 2022)
У статті розглядається розвиток концепції смартспеціалізації з визначенням послідовності і напрямів еволюційних змін, розкривається сутність поняття смартспеціалізації та наводяться результати його термінологічного аналізу. Показано зростання популярності у світі концепції смартспеціалізації, що підтверджено даними про частоту використання терміну «розумна спеціалізація» в глобальному інтернет-просторі та кількість опублікованих робіт, що увійшли в базу Scopus за період 2011-2022 рр. Встановлено передумови та послідовність концептуалізації смартспеціалізації як нового управлінського підходу в системі регіонального управління країн-членів ЄС. Проаналізовано добірку наукових і методичних публікацій розробників і промоутерів концепції смартспеціалізації та зроблено висновок про її теоретико-методологічний розвиток в трьох основних напрямах: конкретизації методології процесу, політичного розгортання та інструментального спрямування. За результатами термінологічного аналізу уточнено сутність смартспеціалізації, включаючи розгляд її смислових основ – «смарт» та «спеціалізація». Акцентовано увагу на зміні предметної сфери спеціалізації з розвитком концепції смартспеціалізації. Наведено авторське бачення концептуального зв’язку понять розумної спеціалізації і диверсифікації. Зроблено висновок про доцільність використання останнього в двох аспектах: як складової процесу смартспеціалізації і його результату. За результатами аналізу та дослідження розвитку концепції смартспеціалізації виділено п’ять смислових конструкцій смартспеціалізації, що розкривають зміст цього полісемічного терміну в різних аспектах, а саме підхід смартспеціалізації, процес смартспеціалізації, стратегія смартспеціалізації, політика смартспеціалізації та смартспеціалізація як інструмент. Розкрито сутність зазначених понять та певний логічний зв’язок між ними. Зроблено висновок про роль і значення смартспеціалізації для української економіки як інструмента згуртування регіональних стейкхолдерів, розвитку інноваційних екосистем і міжрегіонального, транскордонного партнерства, залучення інвестицій задля забезпечення відновлення та розвитку національної економіки на інноваційній основі. The article examines the development of the concept of smart specialisation with determination of the sequence and directions of evolutionary changes, reveals the essence of the concept of smart specialisation and provides the results of its terminological analysis. The article shows the growing popularity of the smart specialisation concept in the world, which is confirmed by the data on the frequency of use of the term "smart specialisation" in the global Internet space and the number of published works included in the Scopus database for the period 2011-2022. The prerequisites and sequence of conceptualisation of smart specialisation as a new management approach in the system of regional governance of the EU member states are established. The article analyses a selection of scientific and methodological publications by developers and promoters of the smart specialisation concept and concludes that its theoretical and methodological development is in three main directions: specification of the process methodology, political deployment and instrumental direction. Based on the results of the terminological analysis, the essence of smart specialisation is clarified, including consideration of its semantic foundations – "smart" and "specialisation". Attention is focused on the change in the subject area of specialisation with the development of the concept of smart specialisation. The author's vision of the conceptual relationship between the concepts of smart specialisation and diversification is presented. It is concluded that it is advisable to use the latter in two aspects: as a component of the smart specialisation process and as its result. Based on the results of the analysis and study of the development of the concept of smart specialisation, five semantic constructions of smart specialisation are allocated, which reveal the content of this polysemic term in various aspects, namely, the smart specialisation approach, the smart specialisation process, the smart specialisation strategy, the smart specialisation policy and the smart specialisation as a tool. The essence of these concepts and a certain logical connection between them are revealed. The author makes a conclusion about the role and importance of smart specialisation for the Ukrainian economy as a tool for uniting regional stakeholders, developing innovative ecosystems and interregional and cross-border partnerships, and attracting investments to ensure the recovery and development of the national economy on an innovative basis.